Can We Praxize Second Language Teacher Education? An Invitation to Join a Collective, Collaborative Challenge - Sharkey, Judy (Íkala, Revista de Lenguaje y Cultura, 2009)
The purpose of this essay is to begin a conversation on how we might make praxis, or ''praxizing,'' i.e., fostering and sustaining an ongoing dialogical relationship between theory and practice, an integral part of second language teacher education. This project is firmly located in critical sociocultural theories of, and approaches to, language learning and teaching, and requires active, participatory and collaborative inquiries by teacher educators and teacher learners across the multiple levels and stages of teacher learning from entry level courses to teaching practica and beyond. Examples of praxis/praxizing are included as well as some of the challenges to doing this work. Received: 14-01-09 / Accepted: 31-03-09 How to reference this article: Sharkey, J. (2009). Can We Praxize Second Language Teacher Education? An Invitation to Join a Collective, Collaborative Challenge. Íkala. 14(2), pp.125-150